Pre-service Teachers’ Perspectives on Materials Development: A Case Study in Florencia, Caquetá, Colombia - Aguilar Cruz, Paola Julie; Garrido-Yagüe, Mónica Fernanda; Rodulfo-Elizalde, Pablo Emilio (Colombian Applied Linguistics Journal, 2025)
This paper presents the findings of a qualitative case study examining pre-service teachers’ perceptions of materials development during their practicum in state high schools. The study involved 15 pre-service teachers from the English Language Teaching Program at Universidad de la Amazonia. Data were collected through surveys, interviews, and artifacts and analyzed using the coding principles of grounded theory. The findings revealed that pre-service teachers perceive materials development as a cornerstone of their practicum experience. They reported that developing materials heightened their awareness of the importance of the practicum. Additionally, they emphasized the need to contextualize materials and integrate technology to enhance students’ learning experience. Nevertheless, findings suggest that pre-service teachers faced several constraints when designing their teaching materials, due to uncertainty about fulfilling their students’ expectations, limited institutional resources, and differing perspectives between cooperating and supervising teachers. These findings have important implications for teacher education programs and material development practices.